Competitive Sports Anxiety among Nepalese National Athletes: Differences by Gender, Sport Type, and Sporting Disciplines - Amatya, Diwakar; Maharjan, Rocky; Pant, Kumari Hira; Bhandari, Shreeram; Koju, Chandan (Mangal Research Journal, 2025)
Sport psychology focuses on the influence of competitive anxiety on performance, despite a paucity of work with athletes in Nepal. The prevalent patterns of sports competition anxiety based on gender, sports type and sporting disciplines are examined in this study. The sample consisted of 496 athletes (281 males and 215 females) who participated in 21 events from the 9th National Games in Pokhara. Competitive anxiety was measured using the Sports Competition Anxiety Test (SCAT). Nonparametric statistical techniques were used as the anxiety scores violated normality assumptions. A Mann–Whitney U test indicated male and female athletes did not show statistically significant differences in anxiety (U = 29701.50, p = .749, r = 0.014). However, athletes competing in individual sports reported significantly higher anxiety than compared to team events (U = 25813, p = .002, r = 0.14). A Kruskal–Wallis test revealed significant differences in anxiety across the 21 sports examined (H = 134.87, p < .001, η² = .27). Kabaddi, Kho- Kho and Archery athletes had the highest anxiety levels, while Football, Rugby and Volleyball athletes had the lowest ones. This implies that competitive anxiety in the athletes of Nepal is more affected not by gender but by sport type and sport-specific demands. The findings emphasize the requirement for targeted psychological assistance, especially for individual and precision-based sportsmen.